(untitled) (Eurasian Journal of Engineering and Technology, 2022)
In this article explores software development for downloading large amounts of data in web applications using the beautiful soup module in the python programming language. Web-scraping is the conversion of large amounts of data into a spreadsheet or API (Application programming interface) using python programming. In the conducted research, was developed software and results were obtained. This software can directly access data in web applications using Hypertext Transfer Protocol or a browser.